Impact of Firm Value on Islamic Reporting Analysis of Sharia Firms in Jakarta Index - Wahyudi, Tri; Sabrina, Nur; Pratiwi, Camka Ayu; Nawawi, Muhammad; Prasadhita, Chandra (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study evaluates the firm's performance in Islamic social reporting. In this study, the independent variable is Islamic Social Reporting. The control variable used in this study is the company's nilai, which is derived from Tobin's Q. In this study, Islamic Social Reporting is treated as a dependent variable. The study's population is based on Syariah companies listed in the Jakarta Islamic Index between 2016 and 2020. The study used purposive sampling to identify 13 out of 30 companies, and data collection was done twice a year. Data evaluation is done using Berganda line regression analysis. It is all stated to indicate that a company's value has a negative impact on Islamic Social Reporting.Peningkatan kinerja keuangan sesuai dengan prinsip syariah di Indonesia is recommended by the Bank Umum Syariah. The study's methodology uses the Proxy Variable ISR, which is a buffer for the ISR index of a few researchers with a total of 48 items for Islamic Social Reporting, and the Proxy Variable Nilai Perusahaan, which uses Tobin's Q, a key indicator in historical accounting.